Exome sequencing identified novel variants in three Chinese patients with 5,10-methenyltetrahydrofolate synthetase deficiency - Xu, Xiaoyan; Zhu, Jing; Fang, Liwei; Zou, Zhuo; Yuan, Jingjing; Peng, Min; Yu, Guoliang; Wu, De; Liu, Yun; Tang, Jiulai (Frontiers in Genetics, 2023)
5,10-methenyltetrahydrofolate synthetase (MTHFS) deficiency is a folate metabolism disorder known as a rare autosomal recessive neurodevelopmental disorder (MIM: #618367). With central nervous system involvements, it is mainly characterized by developmental delay, epilepsy, microcephaly, hypertonia, and cranial nerves involvement. Here, we report three new cases with MTHFS deficiency from two non-consanguineous Chinese families. All patients showed white matter dysplasia and global developmental delay, of which only patient 1 and 2 manifested tonicclonic seizures. Moreover, patient 2 had severe eczema and patient 3 had recurrent diarrhea. Both phenotypic features are firstly found in MTHFS deficiency. Trio whole-exome sequencing and sanger sequencing were used to identify four novel variants, p.Y169Tfs*17, p.S53F, c.117+1delG, and p.E61G in the MTHFS gene. The identification of four novel pathogenic variants and varied clinical features in three affected patients expands the genotype and phenotype spectrum of MTHFS deficiency. We also reviewed all cases of MTHFS deficiency that had previously been reported. The experience of diagnosis and treatment from these cases provides us a more comprehensive understanding of this rare disease.